Investigating the effect of time component on residents\' sense of belonging from two perspectives of age and duration of residence; Case study of Zanjan neighborhoods - Narges Karimi; Farah Habib (تحقیقات کاربردی علوم جغرافیایی)
A sense of belonging to an environment is an emotional connection that takes place between people and the external environment. Many studies have shown that the existence of this connection and its deepening between the person and the environment has a significant role in promoting the physical environment and the emergence of positive social behaviors. Therefore, recognizing the sense of belonging and the factors affecting it and ways to improve it is one of the issues that can lead to the improvement of living conditions and physical environment. Among the many factors that affect the sense of belonging, the time factor as one of these factors can be effective from two perspectives; Duration of residence and age of the environment. In this study, while researching the effect of each of these factors on the sense of belonging of residents, a comparison between these two factors and the intensity of the effect of each on the sense of belonging has been done. The present study is applied in terms of purpose and descriptive-analytical in terms of method. In order to collect the required data and information, library and field methods and questionnaire tools were used. The statistical population of the study consists of citizens living in the six studied neighborhoods in Zanjan. The sample size was estimated to be 300 people using the Cochran's formula. SPSS software was used to analyze the data. The results showed that the sense of belonging in the study areas is moderate to low. The results also showed that the duration of residence and the age of the environment have a positive and significant effect on the sense of spatial belonging and its components. Among the variables, the effect of the environment variable on the sense of spatial belonging is greater than the length of stay, so that the age of the environment predicts 27.1% of the variance of the variable of spatial belonging.